Psychrobacillus vulpis sp. nov., a new species isolated from faeces of a red fox in Spain. - Rodríguez-González, Miguel Ángel; Reina, José Carlos; Béjar, Victoria; Llamas, Inmaculada (Miicrobiology Society, 2019)
A facultative anaerobic, chemoheterotrophic, endospore-forming, Gram-stain-positive rod, designated as strain Z8T , was isolated from red fox (Vulpes vulpes) faeces sampled at Tablas de Daimiel National Park, Ciudad Real, Spain. Strain Z8T grew at 0–37°C (optimum, 28°C), in the presence of 0–5.5% (w/v) NaCl (2.5%, w/v) and at pH 6–10 (pH 7). The strain was motile and positive for catalase, oxidase, H2 S and siderophore production, acid and alkaline phosphatases, and N-acetylglucosamine, adipic acid and malate assimilation. It hydrolysed starch, DNA, l-tyrosine, Tween 20, Tween 80 and lecithovitellin. Phylogenetic analysis of the 16S rRNA gene sequence indicated that strain Z8T is a member of the genus Psychrobacillus, showing high sequence similarity to Psychrobacillus lasiicapitis NEAU-3TGS17T (99.2%) and Psychrobacillus soli NHI-2TT (99.1%), and around 98% to other known species of the genus Psychrobacillus. Digital DNA–DNA hybridization and average nucleotide identity values were lower than 24 and 79%, respectively, with the most related species. In silico G+C content was 35.9mol%. The major cellular fatty acids of strain Z8T were iso-C14:0 , iso-C15:0 and anteiso-C15:0 . The novel strain contained diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol as predominant polar lipids, and the main respiratory isoprenoid quinone was MK-8. Based on the 16S rRNA phylogenetic analysis, together with MLSA (recA, rpoB and gyrB), phylogenomic, chemotaxonomic and phenotypic results, we demonstrate that strain Z8T represents a novel species of the genus Psychrobacillus, for which the name Psychrobacillus vulpis sp. nov., is proposed. The type strain is Z8T (=CECT 9721T =LMG 31001T ).
https://openpolicyfinder.jisc.ac.uk/id/publication/14638
Keywords: Baciláceas; Genomas; Quimiotaxonomía; Filogenia; Zorro rojo - Enfermedades bacterianas; Psychrobacillus vulpis sp. nov; Red fox; Phylogenetic; Chemotaxonomy; Genome; Polyphasic taxonomy